Experimental pragmatics : the making of a cognitive science - Noveck, Ira A., 1962- (Cambridge University Press, 2018)
Explains the phenomena, theoretical debates, experiments and historical development of experimental pragmatics, which investigates how utterances communicate a speaker's intended meaning.